Determining the Effectivity of Infrared Distance to Eliminate Dental Pain Due to Pulpitis and Periodontitis - Silvia Anitasari, - (European Journal of Dentistry, 2020)
Objective The infrared rays is one of the treatments to relief of dental pain due to pulpitis or periodontitis. The ability of infrared to increase the pain threshold which make eliminating P substance on the inflammation area and inducing Aβ and Aδ fibers to activate γ-aminobutyrate (GABA) and neuropeptides to decrease the pain. Hence, reducing or eliminating dental pain. This study to get information about effectively distance between patients and infrared rays which can reduce or eliminate dental pain. Materials and Methods The explorative experimental research to determine the effectivity of the infrared rays’ distance: 45, 55, and 55 cm in reducing or eliminating dental pain. The material of infrared was tungsten with luminous light and the time for the lighting was 15 minutes. Statistical Analysis The data were obtained and analyzed using Wilcoxon’s signed rank test and Kruskal–Wallis test (α= 0.05). Results There were influenced of the infrared rays to reduce the dental pain as follow, distance 45 cm (p = 0.007), distance 55 cm (p = 0.026), and distance 65 cm (p = 0.007). The average scale reduction for distance 45 cm was 2.23 ± 0.83, the distance 55 cm was 3.33 ± 0.87, and the distance 65 cm was (1.78 ± 0.83). Therefore, according to Kruskal–Wallis test with p = 0.004 (p < 0.05) showed the significant difference between the scale to decrease of dental pain was the distance of 55. Conclusion Infrared rays located at a distance of 55 cm from patients might be more effective in relieving dental pain, compared with other distances tested.